2021
DOI: 10.1021/acs.biochem.1c00360
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM Structure of the Photosynthetic LH1-RC Complex from Rhodospirillum rubrum

Abstract: Rhodospirillum (Rsp.) rubrum is one of the most widely used model organisms in bacterial photosynthesis. This purple phototroph is characterized by the presence of both rhodoquinone (RQ) and ubiquinone as electron carriers and bacteriochlorophyll (BChl) a esterified at the propionic acid side chain by geranylgeraniol (BChl a G ) instead of phytol. Despite intensive efforts, the structure of the light-harvesting-reaction center (LH1-RC) core complex from Rsp. rubrum remains at low resolutions. Using cryo-EM, he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…Purple phototrophic bacteria utilize NIR light captured by LH complexes and transfer the energy to the RC BChl dimer (the “special pair”) against an energetically “uphill” gap (“uphill” because LH1 BChls absorb lower-energy wavelengths than do RC BChls); this event initiates photosynthetic charge separation in the special pair followed by subsequent redox events (Figure A). The RC special pair contains only two BChls (in contrast to the 28–34 BChls present in the LH1 complex) and exhibits its Q y band at 860–870 nm although these were obtained from isolated RC-only complexes free of their LH1 component. Recent structural analyses have detected close associations between RC and LH1 complexes, indicating that the special pair’s Q y band peaks reported for RC-only complexes may not be the same as those of the RC in the native LH1–RC. Unfortunately, however, the intensive LH1 Q y band prevents accurate determination of the special pair peak in an LH1–RC complex.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Purple phototrophic bacteria utilize NIR light captured by LH complexes and transfer the energy to the RC BChl dimer (the “special pair”) against an energetically “uphill” gap (“uphill” because LH1 BChls absorb lower-energy wavelengths than do RC BChls); this event initiates photosynthetic charge separation in the special pair followed by subsequent redox events (Figure A). The RC special pair contains only two BChls (in contrast to the 28–34 BChls present in the LH1 complex) and exhibits its Q y band at 860–870 nm although these were obtained from isolated RC-only complexes free of their LH1 component. Recent structural analyses have detected close associations between RC and LH1 complexes, indicating that the special pair’s Q y band peaks reported for RC-only complexes may not be the same as those of the RC in the native LH1–RC. Unfortunately, however, the intensive LH1 Q y band prevents accurate determination of the special pair peak in an LH1–RC complex.…”
Section: Resultsmentioning
confidence: 99%
“…Our light-induced FTIR approach presented here is a potential tool for this purpose and actually supported a conclusion that quinone transport in Tch. tepidum occurs through the spatially restricted hydrophobic channels in the closed LH1 ring. , Recent 3D structural studies of purple bacterial photocomplexes including their mutants have revealed highly diversified LH1 ring structures comprised of 11–17 αβ- or αβγ-subunits with or without a gap, and because of this diversity, a variety of quinone transport pathways are likely. Several groups have resolved cryo-EM structures of LH1–RCs in which the LH1 is comprised of 14 αβ-subunits with a Puf X protein and a previously unrecognized protein U , (or protein Y ,, ), residing at a gap of the C-shaped ring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of the monomeric RC–LH1–PufX–protein-Y complex shows an interesting variation in roles for the 14 LH1 αβ subunits, as opposed to the relatively undifferentiated LH1 subunits found in the RC–LH1 16 complex of Rsp. rubrum , for example [ 6 , 7 ]. In Rba.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 clearly shows that the pigment arrangements in oxygenic photosynthetic complexes contrast sharply with those in photosynthetic bacteria. While the latter seem to prefer rather periodic and ordered pigment arrays (see, for example, [ 10 12 ]), the former rarely show periodic arrangements of pigments. In these systems, chlorophylls (Chls) seem to be placed at random positions with random orientations.…”
Section: Introductionmentioning
confidence: 99%